Islamic Monotheism - "Valiuddin, Mir." (Delhi, 1978)
It is a clear fact that Islam and Islamic ideology invite the ummah or community to monotheism, the belief in the One God. As Muhammad Abduh expresses it, (3z(BThe original meaning of monotheism (tawhid) is the belief that God is one in inalienable divinity. Monotheism was the great aim of the mission of the Prophet Muhammad, the blessings and peace of God be upon him.(3ys
Keywords: Religion